The Effect of Yoga Exercise on Back Pain Reduction of Pregnant Women - Utami, Iis Tri; Astrilia, Ana; Agustina, Rika (Universitas Aisyah Pringsewu, 2022)
Back pain is one of the most common complaints among pregnant women in their third trimester. In Indonesia, back discomfort affects 18% of the population. Yoga is a body, mind, and mental practice that can assist pregnant women in flexing their joints and soothing their brains, especially during the third trimester. The research objective was to recognize the effect of yoga on reducing back pain in the third trimester of pregnant women at the independent midwife practice of Bekti Deka Mardiana in 2021. This research type was quantitative with a pre-experimental design and a one-group pre-test and post-test approach. The participants in this study were all third-trimester pregnant women who had back pains at an independent midwife practice of Bekti Deka Mardiana, in December 2021, with a total of 21 respondents and a sample of 16 people. Purposive sampling was used in the sampling process. Wilcoxon was utilized for data analysis. The results of this research indicate that the average back pain in the third trimester of pregnant women before yoga exercise is 4.94 and after yoga exercise is 1.94. The p-value for the Wilcoxon test was 0.000 less than 0.05. indicating that yoga activity has a p-value of 0.000 for lowering back pain in pregnant women in the third trimester at the independent midwife practice of Bekti Deka Mardiana in 2021. It is suggested that mothers attend programs for pregnant women who hold yoga exercises to avoid back discomfort on a regular basis. Abstrak: Salah satu keluhan ibu hamil yang paling umum di akhir kehamilan adalah nyeri punggung. Prevalensi nyeri punggung di Indonesia adalah 18%. Senam yoga adalah latihan untuk pikiran, tubuh dan jiwa yang membantu ibu hamil menekuk persendian dan menenangkan pikiran, terutama di akhir kehamilan. Tujuan dari penelitian ini adalah untuk mengetahui efektivitas latihan yoga dalam mengurangi nyeri punggung pada ibu hamil di akhir kehamilan di PMB Bekti Deka Mardiana. Jenis penelitian ini adalah kuantitatif dengan menggunakan pre-experimental design dan pendekatan pre-test dan post-test design. Populasi penelitian ini berjumlah 21 orang dan jumlah sampel 16 orang untuk seluruh ibu hamil akhir yang mengalami nyeri punggung bawah di PMB Bekti Deka Mardiana bulan Desember 2021. Teknik sampling yang digunakan adalah Target Sampling. Analisis data menggunakan Wilcoxon Hasil penelitian ini menunjukkan rata –rata nyeri punggung pada ibu hamil trimester 3 yaitu 4,94 sebelum latihan yoga dan 1,94 setelah latihan yoga. Hasil uji Wilcoxon diperoleh p-value sebesar 0,000. Nilai 0,05 berarti latihan yoga efektif menurunkan nyeri punggung pada ibu hamil tua di PMB Bekti Deka Mardiana tahun 2021, dengan p-value 0,000. Disarankan agar ibu hamil dapat menghadiri kelas ibu hamil secara teratur untuk mencegah sakit punggung.